Assessment of the clinical profile and impact of epiphora on quality of life in adult patients in a tertiary hospital of Nepal - Shrestha, Tina; Tamang, Ashish; Balla, Nishtha; Rai, Trishna; Gupta, Madhuri; Shahi, Khushbu (Journal of Chitwan Medical College, 2025)
Introduction: Epiphora or excessive tearing is a common ophthalmologic complaint affecting both ocular function and psychosocial well-being. This study aimed to assess the vision-related quality of life using the Watery Eye Quality of Life questionnaire in patients with epiphora visiting a tertiary care hospital. Method: A cross-sectional study was conducted among adult patients with symptomatic epiphora at the Department of Ophthalmology, Dhulikhel Hospital, Kathmandu University, Nepal. Patients were recruited through consecutive sampling during routine outpatient visits from 04 Apr to 30 Sep 2024. Data were collected through structured interviews, ophthalmic examinations and Watery Eye Quality of Life (WEQOL) questionnaire. Ethical approval was obtained. Statistical analyses were performed using Stata version 17. Descriptive statistics were used to summarise baseline characteristics. Multivariate models were adjusted for age, sex and ethnicity to account for potential confounding factors. A p≤0.05 was considered significant. Result: Out of 103 patients, females were 60(58.3%). Mean age was 39.7±17.9 years. Dry eye syndrome with reflex tearing was found in 53(51.5%), functional epiphora 25(24.3%) and lacrimal obstruction 13(12.6%). Mean WEQOL score was 46.3±11.7, indicating moderate-to-severe impairment. Older age (β=0.1738; p=0.006) and female gender (β=5.212; p=0.02) were independently associated with worse QoL. Eyelid malposition (β=9.28; p=0.048) and lacrimal obstruction (β=7.77; p=0.019) were predictors of poor QoL. Conclusion: Epiphora significantly impairs quality of life, particularly among older adults, females and patients with structural lacrimal or eyelid disorders. Routine QoL assessment using tools like WEQOL may help guide targeted and patient-centred care for epiphora.